A Comprehensive Strategy for Developing Tarung Derajat Towards A Globally Recognized Martial Art - Sheva Tiara Kasih Elda; Ipang Setiawan (Universitas Negeri Semarang, 2025)
Tarung Derajat is an original Indonesian martial arts sport that has developed nationally but has not yet received formal recognition at the international level. This research aims to formulate a comprehensive development strategy to make Tarung Derajat a globally recognised martial art. The research uses a quantitative approach, with a survey administered to Tarung Derajat athletes, coaches, and officials. Data were collected through a questionnaire that had been tested for validity and reliability, covering internal coaching, digital promotion, sports diplomacy, and cultural values. Data analysis was performed using descriptive statistics and multiple linear regression. The research results indicate that internal coaching, digital promotion, sports diplomacy, and cultural values significantly influence the development of Tarung Derajat towards global recognition, both partially and simultaneously. Internal coaching is the most dominant factor. This finding confirms that developing Tarung Derajat to an international level requires an integrated strategy that combines organisational strengthening, the use of digital media, international cooperation, and the preservation of cultural values. This research is expected to serve as a reference for policymakers and sports organisations in promoting the internationalisation of Tarung Derajat.